INVESTIGATION OF A ROLE OF THE IMMUNOGENICITY OF INFLIXIMAB IN THE THERAPY OF ANKYLOSING SPONDYLITIS - O. A. Rumyantseva; A. G. Bochkova; M. M. Urumova; M. V. Cherkasova; E. N. Aleksandrova; S. K. Solovyev; Sh. F. Erdes (Научно-практическая ревматология)
At present, there are a number of unsolved problems associated with unawareness of the causes and ways to prevent the inefficacy of tumor necrosis factor-α  inhibitors.Objective: to study the causes of secondary inefficacy of infliximab (INF), by analyzing its concentrations and antidrug antibody levels in the serum of ankylosing spondylitis (AS) patients receiving long INF,  as well as a possibility to overcome its secondary inefficacy through plasmapheresis.Subjects and methods. 54 patients with active AS (BASDAI > 4) underwent regular long-term  (1-to-10-year) treatment with INF 5 mg/kg according to the standard scheme. During the therapy blood samples were taken before a regular INF infusion to quantify the levels of antibodies to the drug and its concentration. According to the efficiency of the drug, two groups were formed: 1) 27 (50%) patients with INF inefficacy (an exacerbation occurred 2–4 weeks after infusion); 2) 27 patients with drug efficacy. The levels of anti-double stranded DNA antibodies and antinuclear factor were estimated in 27 patients to investigate a relationship between the immunogenicity of INF and the presence of autoantibodies in its secondary inefficacy. A plasmapheresis session was carried out in 5 patients before a regular IFN infusion.Results and discussion. Anti-INF antibodies were found in 28 (52%) patients, these being more common  in the patients with drug inefficacy than in the others (67 and 37%, respectively; p < 0.05). In the patients with INF inefficacy, anti-INF antibody levels were significantly higher than in those with preserved drug effect (18.33 and 4.67 U/ml, respectively; р < 0.05). Moreover, the serum concentration of INF was not significantly different in these groups (1.6 and 2.96 μg/ml). There was an inverse correlation  between INF concentrations and anti-INF antibodies (r = -0.7; p < 0.05). The level of autoantibodies  did not correlate with that of anti-INF antibodies. Following plasmapheresis, the level of anti-INF antibodies dropped in all the patients and the concentration of the drug increased in only three of the five patients; in two of them anti-INF antibody levels were initially low (p < 0.05). Plasmapheresis promoted  a short-term restoration  of INF efficacy no matter what the baseline level of anti-INF antibodies. Conclusion. The secondary inefficacy of INF may be associated with not only the emergence of its neutralizing antibodies and the reduction  in serum drug concentration, but also with other yet unknown causes. There is a need for further investigation of the causes of secondary INF insufficiency and methods for its overcoming.